Fuel cells problems and solutions - Bagotsky, V. S. (Vladimir Sergeevich) (Hoboken, N.J. Wiley, 2012)
"This book extracts the most important information on fuel cells, analyzes it, and assesses its scientific value and technical importance. It provides a full yet concise description of all the important aspects of fuel cells from major types to their historical development to inherent scientific and engineering problems and their commercialization and applications. This edition adds two new chapters, one on structural and wetting properties of porous fuel cell components and the other on fuel cells with mixed reactant supply, and updates all chapters with current knowledge for each topic"-- |c Provided by publisher.
Keywords: Fuel cells